2006
DOI: 10.1079/ivp2006816
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive evaluation of in vitro-stored plants: A comparison of visual and image analysis

Abstract: SummaryIn vitro plants in slow-growth storage require routine evaluation for assessment of viability and need for repropagation. Determination of plantlet health by visual assessment is subjective and varies by genus due to variations in growth pattern and plant structure. Developing a standardized plant evaluation system would improve the efficiency of in vitro storage. This study was initiated to develop digital image analysis techniques for plantlets during slow-growth cold storage and to compare that syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
3
1
1
Order By: Relevance
“…Since the visual evaluation was done on the whole plant and the aim of this project was to compare the visual evaluation with the image analysis, a consistent value was needed for the comparison. This result differs from our earlier study of pear where the lower node was more indicative of change during storage (Aynalem et al, 2006). In neither case was the mean of the two nodes as useful as the individual node.…”
Section: Image Analysis Of In Vitro Stored Hopscontrasting
confidence: 99%
See 1 more Smart Citation
“…Since the visual evaluation was done on the whole plant and the aim of this project was to compare the visual evaluation with the image analysis, a consistent value was needed for the comparison. This result differs from our earlier study of pear where the lower node was more indicative of change during storage (Aynalem et al, 2006). In neither case was the mean of the two nodes as useful as the individual node.…”
Section: Image Analysis Of In Vitro Stored Hopscontrasting
confidence: 99%
“…The goal of this study was to determine if a newly developed imageanalysis procedure developed to detect deterioration for pear shoot cultures (Aynalem et al, 2006) could be applied to cultures of Humulus germplasm and if it could be applied to experimental evaluations. Image analysis was compared to visual observations in an experiment designed to determine if the improved vigor of growthroom plantlets on medium with sequestrene iron would be maintained during cold storage and whether the mean storage duration would change with changes in the iron content of the medium.…”
Section: Introductionmentioning
confidence: 99%
“…Although plant in vitro culture is the basis of most biotechnological methods for breeding and propagation of disease-free plants, very limited research using automated sensors in plant tissue culture has been reported, mainly using “plant to sensor” approaches [ 2 - 7 ] and thus involved a significant degree of invasiveness. So far, only few sensor technologies were used, including monochromatic imaging sensors [ 2 ], RGB cameras [ 3 , 5 - 7 ], modified RGB camera setups with a near infrared (NIR) channel [ 4 , 8 ] and thermal imaging sensors [ 9 ]. Therefore, most studies (reviewed by Gupta and Karmakar [ 5 ]) focused on image analysis to estimate parameters like biomass of callus [ 10 ], classification of somatic embryos and regenerated shoots [ 11 , 12 ], as well as chlorophyll determination [ 13 ] and growth of embryogenic suspension cultures [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Correlating projected plant area to plant height and fresh mass [7] Monitoring plant quality of in vitro conserved plants [8] Ibaraki & Gupta 2011…”
Section: Shoot Culturementioning
confidence: 99%